Elastic Body Spring Method (EBSM) for the Stability Analysis of the Global Vipassana Pagoda in Mumbai, India - Alessandro Gandolfi; Natalia Pingaro; Gabriele Milani (Buildings)
This paper presents an innovative procedure for the stability assessment of masonry domes, aiming at simplifying the modelling and the computational stages of structural analysis. It exploits a macroscopic approach to discretise masonry, specifically using elastic bodies linked by nonlinear interfaces. The latter are made by axial and, when needed, tangential trusses—in turn characterised by an elastic perfectly plastic/brittle behaviour—which constitute the joints connecting homogenised elastic macroblocks. The objective is—by employing low-cost commercial Finite Element software—to predict the behaviour of a masonry curved structure up to failure, maintaining the computational complexity low and the approach accessible to a common user. The process enables not only the quantification of damage at failure but also the tracking of its evolution within the structure, by examining axial forces found in the trusses at each load step. The method allows the modelling of the response of any kind of masonry structure under imposed loads or displacements. Its efficacy is proven on a paradigmatic dome (Global Vipassana Pagoda, Mumbai, India) by comparing the results with limit analysis precedent studies. Finally, the major reliability of a 3D approach is demonstrated.